Efficacy and safety of riociguat in combination therapy for patients with pulmonary arterial hypertension (PATENT studies). (1st July 2020) - Ghofrani, Hossein‐Ardeschir; Grünig, Ekkehard; Jansa, Pavel; Langleben, David; Rosenkranz, Stephan; Preston, Ioana R.; Rahaghi, Franck; Sood, Namita; Busse, Dennis; Meier, Christian; Humbert, Marc
Abstract : Many patients with pulmonary arterial hypertension do not achieve treatment goals with monotherapy, and therefore combination therapy is becoming the standard of care. The soluble guanylate cyclase stimulator riociguat is licensed for the treatment of pulmonary arterial hypertension; here we present findings from patients who were receiving combined riociguat plus endothelin receptor antagonists or non‐intravenous prostanoids in the randomized, placebo‐controlled PATENT‐1 study and its open‐label extension (PATENT‐2). Moreover, we include new data from patients receiving early sequential combination therapy (three to six months of endothelin receptor antagonist treatment) or long‐term background endothelin receptor antagonist therapy (>6 months). Patients were randomized to riociguat 2.5 mg–maximum ( N = 131 pretreated patients) and placebo ( N = 60 pretreated patients). Riociguat improved 6‐min walking distance (PATENT‐1 primary endpoint), functional capacity, and hemodynamics after 12 weeks in pretreated patients. The placebo‐corrected changes in 6‐min walking distance were +24 m in endothelin receptor antagonist‐pretreated patients and +106 m in the small group of prostanoid‐pretreated patients. In the early sequential combination and long‐term background endothelin receptor antagonist groups, the placebo‐corrected changes in 6‐min walking distance were +65 m (95% CI: 17 to 113 m) and +13 m (95% CI: –8 to 33 m), respectively. In conclusion, these data suggest that early sequential combination of an endothelin receptor antagonist plus riociguat is a feasible treatment option. Both early sequential therapy and long‐term background endothelin receptor antagonist plus riociguat were well tolerated in the PATENT studies.